The hydrometeorological sustainability of Miscanthus × giganteus as a biofuel crop in the US Midwest - Roy, Gavin R., author; Kummerow, Christian, advisor; Randall, David, committee member; Barnes, Elizabeth, committee member; Niemann, Jeffrey, committee member; Peters-Lidard, Christa, committee member (Colorado State University. Libraries, 2016)
Miscanthus × giganteus (M. × giganteus) is a dense, 3-5 m tall, productive perennial grass that has been suggested to replace corn as the principal source of biofuel for the US transportation industry. However, cultivating a regime of this water-intensive rhizomatous crop across the US Midwest may not be agronomically realistic if it is unable to survive years of low precipitation or extreme cold wintertime soil temperatures, both of which have previously killed experimental crops. The goal of this research was to use a third-generation land surface model (LSM) to provide a new assessment of the hypothetical biogeophysical sustainability of a regime of M. × giganteus across the US Midwest given that, for the first time, a robust and near-complete dataset over a large area of mature M. × giganteus was available for model validation. Modifications to the local hydrology and microclimate would necessarily occur in areas where M. × giganteus is adapted, but a switch to this biofuel crop can only occur where its intense growing season water usage (up to 600 mm) and wintertime soil temperature requirements (no less than -6° C) are feasibly sustainable without irrigation. The first step was to interpret the observed turbulent and ecosystem flux behavior over an extant area of mature M. × giganteus and replicate this behavior within the SiB3 third-generation LSM (Simple Biosphere Model, version 3). A new vegetation parameterization was developed in SiB3 using several previous empirical studies of M. × giganteus as a foundation. The simulation results were validated against a new, robust series of turbulent and ecosystem flux data taken over a four-hectare experimental crop of M. × giganteus in Champaign, IL, USA from 2011-2013. Wintertime mortality of M. × giganteus was subsequently assessed. It was proposed that areas with higher seasonal snowfall in the US Midwest may be favorable for M. × giganteus sustainability and expansion due to the significant insulating effect of snow cover. Observations of snow cover and air and soil temperatures from small experimental plots of M. × giganteus in Illinois, Wisconsin, and the lake effect snowbelt of southern Michigan were analyzed during several anomalously cold winters. While a large insulating effect was observed, shallow soil temperatures were still observed to drop below laboratory mortality temperature thresholds of M. × giganteus during periods of snow cover. Despite this, M. × giganteus often survived these low temperatures, and it is hypothesized that the rate of soil temperature decrease might play a role in wintertime rhizome survival. The domain was expanded in SiB3 to cover the US Midwest, and areas defined as cropland were replaced with the developed M. × giganteus surface parameterization. A 14-year uncoupled simulation was carried out and compared to an unmodified simulation in order to gauge the first-order hydrometeorological sustainability of a large-scale M. × giganteus regime in this area in terms of simulated productivity, evapotranspiration, soil water content, and wintertime cold soil temperature. It was found that M. × giganteus was biogeophysically sustainable and productive in a relatively small portion of the domain in southern Indiana and Ohio, consistent with a small set of previous studies and ultimately in disagreement with the theory that M. × giganteus could reliably replace corn in areas such as Illinois and Iowa as a profitable and sustainable biofuel crop.